Lamiaceae endemic from Peru - León, Blanca (2006)
The Zamiaceae are represented in Peru by four species in the genus Zamia (Brako & Zarucchi, 1993; Stevenson, 2004), all shrubs with stems less than 2 m high or with a subterranean stem. In this book we recognize two endemic species, both additions to the flora since 1993 (Ulloa Ulloa et al., 2004). These endemic species are found in lowland Amazonian forests and in the foothills of the montane forest, between 100 and 700 m elevation. One species has been registered within Peru’s protected areas network. Due to their handsome foliage, species of this family are valued as ornamentals and some populations are affected by illegal extraction for commercial sale.